2008
DOI: 10.1159/000167873
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Bacteremia in Hemodialysis: Which Preventive Measures to Take?

Abstract: Background: The use of tunneled hemodialysis catheters as definitive vascular access is becoming increasingly more widespread, reaching 25% of all dialysis patients in some countries. The rate of infectious morbidity and mortality is much higher when catheters are used than when patients are dialyzed through grafts or native fistulas, and it is generally agreed that implementing appropriate preventive measures would do more to lower its incidence. Methods: A prospective, randomized, open-label, long-term follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Some authors proposed antibiotic or antiseptic ointments at the exit site. Antibiotic ointment at the exit site was compared in one randomized study to gentamicin CLS (5 mg/ml) [20] . CRI was less frequent in the gentamicin CLS group.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors proposed antibiotic or antiseptic ointments at the exit site. Antibiotic ointment at the exit site was compared in one randomized study to gentamicin CLS (5 mg/ml) [20] . CRI was less frequent in the gentamicin CLS group.…”
Section: Discussionmentioning
confidence: 99%
“…Another opinion review reported conflicting results of trials made by different authors with different citrate concentrations and for sure with different clinical management practices, which in our opinion are not comparable. In our hands, topical antimicrobial ointments had a significantly higher number of CRB episodes compared to gentamicin lock and the addition of topical antimicrobial ointments to gentamicin lock did not decrease the incidence of CRB . So our experience with Lok's recommendation of prophylactic topical antimicrobial ointments at the catheter exit site had no utility.…”
Section: Discussionmentioning
confidence: 60%
“…No additive effect was observed when joining both methods in the same patients. The number of CRB episodes was three times lower in the low‐dose gentamicin lock group and five times lower when compared to our historical controls . Most popular locks use either gentamicin or citrate.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations